Mother's Experience in Caring for Children with Special Needs: A Literature Review - Rahmatuz Zulfia (Indonesian Journal of Disability Studies, 2020)
Children with special needs experience long-term limitations on physical, mental, social, and emotional aspects which also have an impact on family well-being, both physical and mental. The impact of parenting on children with special needs is especially felt by mothers, as main caregivers and sources of child support. Anticipation of the acceptance and support system for mothers is needed so that the potential and quality of life children with special needs can be achieved optimally The purpose of this literature review is to know the mothers experience in carrying out their caregiving role in caring for children with special needs. This literature study was conducted by collecting articles from online database that published between 2015 - 2019. The analysis showed that the experience of mothers caring for children with special needs was experienced before the diagnosis, during the diagnosis, and after the diagnosis. The most experienced mother's is the experience after diagnosis, they are feelings within oneself, physical and mental health, high care burden, social isolation, maternal care, maternal needs in carrying out the caregiving role, obstacles in carrying out the caregiving role, and positive aspects from caring for children with special needs. Nurses as health professionals who provide comprehensive interventions are expected to provide attention and assistance to mother, since before until the diagnosis is established, so that the mothers and children well-being can be achieved optimally.